Cross-contamination of carbapenem-resistant Gram-negative bacteria between patients and the hospital environment in the first year of a newly built surgical ward - Boutin, Sébastien; Scherrer, Martin; Späth, Isabel; Kocer, Kaan; Heeg, Klaus; Nurjadi, Dennis (The journal of hospital infection, 2024)
Background - Transmission and outbreaks of carbapenem-resistant Gram-negative bacteria (CRGN) in hospitals are often associated with contamination of the wastewater environment. We performed a prospective observational study to investigate the colonization of the hospital wastewater environment during the first year of occupancy of the surgical intermediate and intensive care units of a newly constructed building at the University Hospital of Heidelberg, Germany. - Methods - We performed monthly screening of the wastewater system (toilets and sinks) for 12 months, starting 1 month before opening (1st October 2020 to 30th October 2021). Admission and weekly rectal screening of patients for CRGN were also performed in parallel. Bacterial isolates were characterized by whole-genome sequencing. - Results - Twenty-seven of 1978 (1.4%) admitted patients were colonized/infected with CRGN. A total of 29 CRGN isolates from 24 patients and 52 isolates were available for sequencing. Within the first month of occupancy, we identified seven patients colonized/infected with CRGN, while none were found in the environmental reservoirs. The first detection of CRGN isolates in the sewage system started five months after the first occupancy. Two previously non-colonized patients were colonized/infected with Pseudomonas aeruginosa strains colonizing the sewage system. The significant identity of plasmids carrying the carbapenemase gene suggests that long-term colonization of the sewage system facilitates the emergence of new carbapenem-resistant clones. - Conclusion - Cross-contamination between patients and the hospital environment is bidirectional. Our study demonstrated that contamination of the hospital wastewater environment may lead to persistent colonization and may serve as a reservoir for nosocomial acquisition of CRGN.